Embedding Health and Well-Being in Value Statements of Canada’s Post-Secondary Institutions: A Mixed Methods Study - Thaivalappil, Abhinand; Stringer, Jillian; Young, Ian; Burnett, Alison; Bhattacharyya, Anit; Papadopoulos, Andrew (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2024)
Many post-secondary institutions contain organizational values, which describe enduring beliefs that support strategic priorities and guide members of an organization. Relatedly, the adoption of health-promoting frameworks calls on embedding health within post-secondary institutions’ core values. The study objective was to map Canada’s post-secondary values to determine how health is integrated within value statements. Mixed methods were used to map institutional values, contextualize well-being, and identify thematic messages of health-related content contained within values. Most institutions espoused values (n = 64, 71%), yet only a small proportion of these institutions espoused health within their value statements (n = 7, 11%). Qualitative analysis revealed three thematic messages: (i) health as a descriptor for other institutional priorities, (ii) wellness broadly acknowledged or embedded within non-health values, and (iii) well-being as a core value or commitment. These novel findings suggest more institutions must embed health as a core value to demonstrate institutional commitment.